Bringing The Daily Mail to Africa: entertainment websites and the creation of a digital youth public in post-genocide Rwanda. Issue 1 (2nd January 2019) - Grant, Andrea Mariko
ABSTRACT: This article considers Kinyarwanda-language entertainment websites in Rwanda and argues that they create an alternative digital youth public. In a context wherein the 'traditional' media is heavily regulated, I argue that these websites provide important spaces of debate, aspiration, and self-making. They allow young Rwandans to participate in transnational networks of cultural production and imagine themselves as well-connected and 'modern' global citizens. This does not mean, however, that the digital public convened by these websites is a space of 'rational' or democratic debate. Rather, these sites are heavily gendered and seem disproportionately concerned with policing the behaviour and dress of young women. In doing so, they reveal on-going anxieties about women's sexuality and place in the public sphere. Furthermore, as much as entertainment websites are understood to be relatively 'apolitical', they are inevitably shaped by the country's politics. The digital youth public convened by entertainment websites is 'alternative' insofar as it allows for vibrant debate on topics of importance to young people, but it should in no way be seen as existing outside the realm of state power.